Kaikana Coffee & Kitchen Website UI: A Design Thinking Approach - Santoso, Diesya Latifa; Caesaron, Dino; Yekti, Yusuf Nugroho Doyo (School of Industrial and System Engineering, Telkom University, 2025)
The rapid growth of the café industry demands innovative approaches to remain competitive. This study proposes a user interface (UI) design for the Kaikana Coffee & Kitchen website using the Design Thinking methodology to improve marketing effectiveness. The research applies the five-stage Design Thinking process—Empathize, Define, Ideate, Prototype, and Test—to design a user-centric interface that enhances customer engagement and simplifies online interactions. Surveys involving 30 customers and interviews with the café owner informed us of the design. The final prototype was evaluated using the System Usability Scale (SUS), yielding an average score of 82.75, indicating a high level of usability. The results suggest that a professionally designed website can significantly enhance customer satisfaction, improve sales performance, and strengthen brand identity. Future work should focus on broader user testing and integration with e-commerce functionalities.